A Randomized Clinical Trial Comparing Three Different Exercise Strategies for Optimizing Aerobic Capacity and Skeletal Muscle Performance in Older Adults: Protocol for the DART Study - Tavoian, Dallin; Russ, David W.; Law, Timothy D.; Simon, Janet E.; Chase, Paul J.; Guseman, Emily Hill; Clark, Brian C. (Frontiers in Medicine, 2019)
Background: Age-related declines in physical function lead to decreased independence and higher healthcare costs. Individuals who meet the endurance and resistance exercise recommendations can improve their physical function and overall fitness, even into their ninth decade. However, most older adults do not exercise regularly, and the majority of those who do only perform one type of exercise, and in doing so are not getting the benefits of endurance or resistance exercise. Herein we present the study protocol for a randomized clinical trial that will investigate the potential for high-intensity interval training to improve maximal oxygen consumption, muscular power, and muscle volume (primary outcomes), as well as body composition, 6-minute walk distance, and muscular strength and endurance (secondary outcomes). Methods and Analysis: This is a single-site, single-blinded, randomized clinical trial. A minimum of 21 and maximum of 30 subjects aged 60-75 that are generally healthy but insufficiently active will be randomized. After completion of baseline assessments, participants will be randomized in a 1:1:1 ratio to participate in one of three 12-week exercise programs: stationary bicycle high-intensity interval training, stationary bicycle moderate-intensity continuous training, or resistance training. Repeat assessments will be taken immediately post intervention. Discussion: This study will examine the potential for stationary bicycle high-intensity interval training to result in both cardiorespiratory and muscular adaptations in older adults. The results will provide important insights into the effectiveness of interval training, and potentially support a shift from volume-driven to intensity-driven exercise strategies for older adults.